Pregled ureditve igrišč vrtcev v ljubljanski zdravstveni regiji - Svetičič Marinko, Jana (Zdravstveno varstvo, 2009)
Background: Health and safety are two important attributes of nursery schools.Playgrounds are an integral part of the nursery school complex. It is very important that playgrounds constitute an environment that ensures health,safety and welfare of children. Some sections of "Technical norms and minimum requirements for nursery schools" (Official Gazette of the Republic ofSlovenia No. 73/2000 and No. 75/2005) deal with playground safety policies, and some other with playground site, layout and equipment.The Institute of Public Health advises nursery schools in the region on how to fulfill these regulations, and those responsible for advising should be fully informed aboutthe situation concerning local nursery school playgrounds. Methods: The questionnaire asked questions related to playground regulations. The sample studied consisted of 66 randomly selected nursery schools from the Ljubljana healthcare region. Survey with inspection of all playgrounds in the sample wascarried out in the field and, at a later stage, via telephone. Results: Thecollected data showed that 97% of the nursery schools surveyed had fenced playgrounds, yet not all fences complied with safety regulations: some were too low and did not prevent climbing, and two-thirds had no self-closing gatesand were therefore not suitable for playgrounds. Only one third of stairsin playgrounds were visibly marked. Conclusion: The study assessed the appropriateness and safety of playgrounds in the sample. The shortcomings werediscussed with the nursery school management in order to find viable solutions to the problems. In two cases the local community was asked for financial support.
Keywords: igrišča; Ljubljana; urejenost; vrtci